A cointegration analysis of nifty index with sectoral indices of NSE. Issue 6 (18th August 2022) - Kumar, Santosh; Patel, Ajay; Garg, Sandeep
Abstract: The study aims to examine the short run and long run relationship between bank nifty and other selected sectoral indices of NSE. 10 sectoral indices e.g. Current research has taken into account Nifty Bank, Nifty Auto, Nifty IT, Nifty FMCG, Nifty Media, Nifty Metal, Nifty Pharma, Nifty PSU, Nifty Private Banks, and Nifty Reality. We used the Unit Root Test, VAR, Descriptive Analysis, Johansen's Cointegration Test, Beta, and VECM to test our hypothesis. According to the study, there is no long-term association between the variables and the data was not steady at the level.Only short term relationship was seen between NIFTYINDEX and RETNIFTY_MEDIA. Beta justified that Nifty Pharma is most defensive sector i.e. it is least sensitive to changes occurring to Nifty, whereas Nifty Private bank is most sensitive sector. It was also seen that 3 sectors, Nifty_ Media, Nifty_PSU, and Nifty Pharma Indexes have negative correlation with Nifty Index.